The Effectiveness of Health Education Using Powerpoint and Audio Visual Media on Increasing the Knowledge of Women of Reproductive Age About Cervical Cancer in the Working Area of Gandasuli Public Health Center, South Bacan District in 2023 - Marwah Marwah; Rifzul Maulina (Jurnal Siti Rufaidah, 2025)
The incidence of hypertension at the Tadoy Community Health Center was 29.4%. Based on the Tadoy Community Health Center Report in 2023, there were 78 cases of hypertension in pregnant women, dominated by pregnant women with HDK (50%). The short-term impact of hypertension during pregnancy can affect both the mother and the fetus. In addition to medication, therapy for pregnant women with hypertension can be given by soaking the feet in warm water and regularly consuming Ambon bananas. The purpose of this study was to determine the effect of warm water therapy and Ambon banana consumption on reducing blood pressure in pregnant women with hypertension. This type of research used a qualitative research method with a case study approach. This activity was carried out on two pregnant women with hypertension at the Tadoy Community Health Center. Providing warm water therapy was effective in reducing blood pressure in pregnant women from 150/90 mmHg at the first visit to 130/85 mmHg at the second visit and to 120/75 mmHg. Consuming bananas was also effective in reducing blood pressure from 150/90 mmHg at the first visit to 140/90 mmHg at the second visit and to 120/80 mmHg. There was a difference in effectiveness between warm water therapy and consuming Ambon bananas in reducing blood pressure in hypertensive pregnant women, where warm water therapy was more effective than Ambon bananas in lowering blood pressure. It is hoped that the results of this study can help lower blood pressure by soaking feet in warm water, so that pregnant women can do it independently and can reduce risks in pregnancy.